Association between Body Mass Index and Bone Mineral Density in Patients Referred for Dual-Energy X-Ray Absorptiometry Scan in INMAS, Sylhet (Bangladesh Journal of Nuclear Medicine, 2021)
With an aging population, osteoporosis is increasingly becoming a public health concern. Bangladesh has a high incidence of osteoporosis and occurs among a relatively younger age group than in the developed world. There are several factors that could be associated with bone mineral density (BMD). We are keen to determine the association with BMD and BMI. The study was carried out on 152 patients who were referred to INMAS for dual energy X- ray absorptiometry (DEXA) measurement of bone mineral density (BMD) during the periods of January 2018 to July 2019. BMD was measured at right femoral neck and lumbar spines. Data about age and sex, BMI were recorded. Reporting was done according to the T score following WHO criteria. Prevalence were compared using chi-squared tests. Among 152 patients, 84.9% were females and 15.1% were males. Results showed for right femur that normal bone density in 91 (59.1%), osteopenia in 54 (35.1%), osteoporosis in 9 (5.8%) and BMD in spine was normal in 57 (37.0%) osteopenia in 44 (28.6%), osteoporosis in 53 (34.4%). About 60% of the study population was normal weight and others were underweighted or overweighed. Status of BMD was associated with BMI in the lumbar spine and femur. In this study group, total 61.2% and 26.3%were found low BMD in spine and right femur respectively. In age group ≥ 60 years, low BMD in spinewas 72.0% that is 42.29% higher compare to below 60 years’ group (50.6%).Correlation of BMI with lumbar spine T score, right femur and left femur T score were measured by Pearson’s correlation coefficient test. Positive significant Pearson’s correlation was observedbetween BMI with spine T score (r = 0.397; p =